THE EFFECTS OF GRAMMAR MASTERY TOWARDS STUDENTS’ READING COMPREHENSION - Fitriyeni Fitriyeni; Tri Widyastuty (Yayasan Akrab Pekanbaru, 2018)
The aim of the research is to know the effects of grammar mastery towards student’s reading comprehension.Grammar has an important role in mastering a language, and comprehending reading is also one of the ways to improve language learning. Therefore, it is necessary to know whether both variables have significantly effect to each other. Research methodology used is descriptive quantitative study. Sample are taken 80 students, and the sample taken with random technique. Data was collected through multiple choice test to the samples. Data analysis uses descriptive statistics. The research result shows that grammar mastery has a significant effect or influence towards the improvement of student’s reading comprehension. In other words the students who guided better grammar mastery are better to comprehend reading. Learning a language can hardly be defined from its grammatical. The language is mastered when the students can use it correctly and comunicatively either in oral or written. Thus, in learning English, the students must engage well to its grammatical. The results contribute most to the increasing of student’s reading comprehension. Key words: Grammar, Grammar Mastery, Language Learning, Reading Comprehension